Visualization of gold and platinum nanoparticles interacting with Salmonella Enteritidis and Listeria monocytogenes - Ewa Sawosz (Dove Medical Press, 2010)
Ewa Sawosz1, André Chwalibog2, Jacek Szeliga3, Filip Sawosz2, Marta Grodzik1, Marlena Rupiewicz1, Tomasz Niemiec1, Katarzyna Kacprzyk11Division of Biotechnology and Biochemistry of Nutrition, Warsaw University of Life Sciences, Warsaw, Poland; 2Department of Basic Animal and Veterinary Sciences, University of Copenhagen, Copenhagen, Denmark; 3Division of Microbiology of Analytical Centre, Warsaw University of Life Sciences, Warsaw, PolandPurpose: Rapid development of nanotechnology has recently brought significant attention to the extraordinary biological features of nanomaterials. The objective of the present investigation was to evaluate morphological characteristics of the assembles of gold and platinum nanoparticles (nano-Au and nano-Pt respectively), with Salmonella Enteritidis (Gram-negative) and Listeria monocytogenes (Gram-positive), to reveal possibilities of constructing bacteria-nanoparticle vehicles.Methods: Hydrocolloids of nano-Au or nano-Pt were added to two bacteria suspensions in the following order: nano-Au + Salmonella Enteritidis; nano-Au + Listeria monocytogenes; nano-Pt + Salmonella Enteritidis; nano-Pt + Listeria monocytogenes. Samples were inspected by transmission electron microscope.Results: Visualization of morphological interaction between nano-Au and Salmonella Enteritidis and Listeria monocytogenes, showed that nano-Au were aggregated within flagella or biofilm network and did not penetrate the bacterial cell. The analysis of morphological effects of interaction of nano-Pt with bacteria revealed that nano-Pt entered cells of Listeria monocytogenes and were removed from the cells. In the case of Salmonella Enteritidis, nano-Pt were seen inside bacteria cells, probably bound to DNA and partly left bacterial cells. After washing and centrifugation, some of the nano-Pt-DNA complexes were observed within Salmonella Enteritidis.Conclusion: The results indicate that the bacteria could be used as a vehicle to deliver nano-Pt to specific points in the body.Keywords: morphology, nanoparticles, gold, platinum, bacteria